Pengembangan Bahan Ajar Menyimak Bahasa Indonesia bagi Penutur Asing (BIPA) Berbasis Video Animasi di KBRI Ankara - Suhendra, Nadha Nuur Annisa; Muliastuti, Liliana; Eriyani, Reni Nur (Jurnal Bahasa dan Sastra, 2024)
This study developed teaching materials to improve listening skills for learners of Indonesian as a Foreign Language (BIPA) at the Indonesian Embassy in Ankara. Following Thiagarajan's 4D model (Define, Design, Develop, Disseminate), a needs analysis identified learner requirements. The design phase focused on creating materials, particularly animated videos, to enhance listening comprehension. Development involved creating the materials and obtaining feedback from subject matter and media experts for BIPA 1 learners. Dissemination included internal validation by BIPA instructors and user testing with learners and teachers. Validation results from subject matter and media experts categorized the materials as "Feasible" and "Very Feasible," respectively. User feedback yielded an average score of "Very Feasible." These findings suggest the developed materials are highly suitable for enhancing BIPA 1 listening skills at the Indonesian Embassy in Ankara.